2014
DOI: 10.3797/scipharm.1404-09
|View full text |Cite
|
Sign up to set email alerts
|

New Activity of a Protein from Canavalia ensiformis

Abstract: Concanavalin A is a legume lectin which preferentially agglutinates transformed cells and shows antitumor effects on human breast carcinoma cells in vitro and in vivo. It is considered as a new potential antineoplastic agent targeting apoptosis, autophagy, and anti-angiogenesis in preclinical or clinical trials for cancer therapeutics, which has recently become the object of intensive study. In the present investigation, we show the capacity of the lectin to bind manganese, gold, iron, and zinc porphyrins: all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, deregulatory autophagy was associated with tumorigenesis, and has been recommended as antitumor therapy. More and more studies have shown that autophagy activity was altered in a variety of human tumor cells [5][6][7]. It should be noted that autophagy may also have antitumor effect in some circumstances, whereas autophagy can also protect tumor cells from destruction under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, deregulatory autophagy was associated with tumorigenesis, and has been recommended as antitumor therapy. More and more studies have shown that autophagy activity was altered in a variety of human tumor cells [5][6][7]. It should be noted that autophagy may also have antitumor effect in some circumstances, whereas autophagy can also protect tumor cells from destruction under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the original use of lectins in vaccination protocols has been expanded to other applications. Hence, besides its use as therapeutic agents in infectious and parasitic diseases, lectins have been applied as new potential antineoplastic agents targeting apoptosis, autophagy, and anti-angiogenesis in preclinical or clinical trials for cancer therapeutics, and in neurodegenerative disorders, as well (Alegre-Maller et al, 2014; Bogoeva et al, 2014; Aminou et al, 2016; Barbosa-Lorenzi et al, 2016; Dar et al, 2016; Freitas et al, 2016; Ricci-Azevedo et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, T/Tn specific lectins have been identified as potential targeting molecules [29]. The non-covalent binding of porphyrins to lectins was well studied [30, Bogoeva, 2010 #314], particularly the interaction of wheat germ agglutinin (WGA) [31][32][33][34] and Con A with porphyrins was evaluated and affinity constants in micromolar range were calculated, accordingly [35,36].…”
Section: Why Lectins Are Useful Tools For the Targeted Therapy?mentioning
confidence: 99%